Career Development for Police Personnel at The North Kalimantan Provincial Police Department Based on Competency and Assessment Center - Reva Tiono Saputra; Lamhot Henry Pasaribu (SAFE-Network, 2026)
This study aims to analyze the influence of personnel competency and assessment centers on the career development of police officers at the North Kalimantan Regional Police Department (Polda Kaltara). Using a quantitative explanatory design, this research collected data from 110 respondents selected through simple random sampling. The instruments passed validity and reliability tests, and the regression model met all classical assumptions, ensuring its robustness. The results show that personnel competency has a positive and significant effect on career development, indicating that higher levels of knowledge, skills, and professional behavior improve opportunities for promotion and job mobility. Likewise, the assessment center also demonstrates a significant positive effect, confirming its role as an objective and merit-based evaluation mechanism in personnel selection and promotion processes. Simultaneously, both variables contribute 17.9% to explaining career development, while the remaining influence is derived from factors outside the model. These findings highlight the strategic importance of integrating competency frameworks and assessment centers to strengthen human resource governance within the Indonesian National Police, particularly in regions with complex security dynamics such as North Kalimantan. The study provides practical recommendations for expanding assessor training, increasing technology utilization, and enhancing competency-based personnel development programs to support Polri’s bureaucratic reform agenda.